Knowledge assets and bilateral-trade flows in ASEAN-5 countries : an extension of gravity panel data model - Mohd Fairuz Md. Salleh,; Wan Sallha Yusoff,; Norida Basnan,; Tengku Suriani Tengku Yaacob, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study analyses knowledge asset as a determinant factor to bilateral trade flows in ASEAN-5 countries, namely, Singapore, Malaysia, the Philippines, Indonesia and Thailand from 2000 to 2015. The gravity model of trade is extended by incorporating the five components of knowledge assets, namely, national’s market capital, financial capital, renewal and development capital, human capital and process capital as explanatory variables. The empirical investigation is based on pooled ASEAN-5 data and done using random effects and fixed effects models. The principle findings corroborate that knowledge assets are positive and have significant effects on bilateral trade flows in ASEAN-5 countries. The consideration of improving human capital and financial capital is vital given that it is a major contribution to the changes of bilateral trade in ASEAN. This study is open for further research on the negative and significant influences of process capital towards bilateral trade flows in ASEAN-5 countries.